DESAIN MEDIA GAMES QUIZ BOX WORD WALL NET PADA MATERI MEYAKINI KITAB-KITAB ALLAH DI KELAS VIII - Luqman Hakim, Muhammad; Ainur Rafiq, Muhammad (Universitas Cokroaminoto Palopo, 2024)
This research aims to develop more interactive and interesting learning media for Class VIII SMP students in Islamic Religion subjects regarding the material of believing in the books of Allah. The media developed is based on educational games using the wordwall.net platform with box and open box quiz games. Media development follows the research and development model which consists of analysis, design, development, implementation and evaluation stages. Validation was carried out by media and material experts, as well as small group trials to determine student responses. The result is a media word wall that is suitable for use based on the validators' criteria. Implementation in the classroom shows a significant increase in student learning outcomes. The learning process becomes more dynamic and students seem enthusiastic about learning through a game format on the wordwall. This media turned out to be effective in conveying material about faith in Allah's books in an interesting and in-